PENERAPAN MODEL POLA KESEHATAN FUNGSIONAL GORDON TERHADAP TERIDENTIFIKASINYA MASALAH KEPERAWATAN KOMPREHENSIF PADA PASIEN DIABETES MELLITUS - Wiratmo, Puji Astuti; Zakiyah; Narulita, Sari (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Patient with Diabetes ulcer/gangrene require a long period of treatment so that various nursing problems can arise including physical, psychological, social and spiritual problems related to the patient's response to the illness. Research conducted by Sofiana, et al (2012) of hospitalized patients with diabetic ulcers at Arifin Ahmad Hospital in Pekan Baru shows the results that more than 50% of patients experience psychosocial problems including low self-esteem, negative body image, negative self-concept, self-ideal irrelevant and high stress levels. Referring to the philosophy of nursing where nursing believes that humans and humanity are the central point of every health care effort and that human is a whole and unique creature of God Almighty that consist of bio-psycho-socio-spiritual and cultural aspects. Therefore, to be able to carry out their lives, human needs must be met in a balanced way that includes bio-psycho-socio-spiritual and cultural. Objective:The purpose of this study was to identify comprehensive nursing problems in nursing assessment by the Gordon Functional Health Pattern Model in Diabetic ulcer / gangrene patients. Methods: This is a quantitative descriptive research with survey for the design. 20 Diabetic patient with ulkus or gangrene recruited as the sample though total sampling technique. Results:Based on research conducted on 20 diabetic ulcer / gangrene patients in the medical nursing ward of Budi Asih Regional Hospital found that nursing problems in each of Gordon's functional health patterns can be identified. Conclusion: .Nursing assessment with Gordon's pattern is able to identify the patient's nursing problems comprehensively in the biopsychososiospiritual aspects